Electrothermal Microactuators With Peg Drive Improve Performance for Brain Implant Applications - Anand, Sindhu (2012)
This paper presents a new actuation scheme for in-plane bidirectional translation of polysilicon microelectrodes. The new Chevron-peg actuation scheme uses microelectromechanical systems (MEMS) based electrothermal microactuators to move microelectrodes for brain implant applications. The design changes were motivated by specific needs identified by the in vivo testing of an earlier generation of MEMS microelectrodes that were actuated by the Chevron-latch type of mechanism. The microelectrodes actuated by the Chevron-peg mechanism discussed here show improved performance in the following key areas: higher force generation capability (111 μN per heat strip compared to 50 μN), reduced power consumption (91 mW compared to 360 mW), and reliable performance with consistent forward and backward movements of microelectrodes. Failure analysis of the Chevron-latch and the Chevron-peg type of actuation schemes showed that the latter is more robust to wear over four million cycles of operation. The parameters for the activation waveforms for Chevron-peg actuators were optimized using statistical analysis. Waveforms with a 1-ms time period and a 1-Hz frequency of operation showed minimal error between the expected and the actual movement of the microelectrodes. The new generation of Chevron-peg actuators and microelectrodes are therefore expected to enhance the longevity and performance of implanted microelectrodes in the brain.  [2011-0341]